A Rare Normal Variant with an Unusual Presentation on a Male Mammogram: A Case Report - Victoria Kai Lin Tay; Si Ying Tan; Chow Yin Wong; Lester Chee Hao Leong (Journal of the Korean Society of Radiology)
The sternalis muscle is a rare supernumerary muscle representing a normal anatomical variant in the anterior thoracic musculature. Due to wide variation in its morphology and relative unfamiliarity among radiologists, it has been implicated in the misdiagnosis of breast masses on mammography. A 23-year-old male with no significant medical history was referred to our institution for further management of painless bilateral breast enlargement since adolescence. Physical examination revealed breasts of slightly prominent size but there was no palpable breast lump. Mammography work-up found symmetrical, well-defined soft tissue masses projected over the posteromedial aspect of both breasts. Imaging findings were consistent with bilateral sternalis muscles, unusually hypertrophic in size due to intense upper body weight training by the patient. This case highlights the importance of recognizing the usual and unusual presentations of the sternalis muscles on mammography to avoid any unnecessary work-up.